Needs Analysis of Contextual Training for Automotive Technicians - Andriyani, Eka; Wirasti, R.A Murti Kusuma; Muslim, Suyitno (LPPM Undiksha, 2020)
The advancement of technology make automotive industry has to improve rapidly, it causes the training for technicians must be update continuously, so it confuses some instructors it caused some of these trainings often ineffective, they are not what the company truly needs. This study aims to analyze the needs to make an effective training in the automotive industry. This method was developed to minimize errors that would occur while develop a training for technicians. This study used a qualitative approach, the data to be studied were collected through interviews with technicians and instructors, literature review also used in this study. The results of this study is to produce a needs analysis method that considers aspects of learning according to context in order to keep up with technology advancement. A training can be effective if the needs of the company were fulfilled, utilizing learning facilities that company already has can also increase the training development process. The contribution of the results of this research to the field of educational technology is a method for analyzing training needs specifically for technicians in order to assist other researchers in field of educational technology to develop training for technicians.